Collocational competence among Malaysian undergraduate law students - Kamariah, Yunus
This study aims to investigate collocational competence among undergraduate law students at University Sultan Zainal Abidin, Terengganu, formerly known as University Darul loran Malaysia (UDM) through accurate and inaccurate production of collocations of prepositions in the learners' production of the colligations in the Problem Question essays focusing on Law of Contract genre, and to explore their use of the functions relational to the content of law. The findings showed that the learners still produced colligation errors despite their competence in observing the communicative and discoursal functions of legal discourse. This study recommends an explicit teaching of collocations of prepositions to increase their awareness to these patterns besides the establishment of English for Academic Legal Purposes (EALP) courses at every institution.